(untitled) (Clinics, 2021)
This study aimed to systematically review the literature to assess the effect of preemptive intravenous ibuprofen on pain reduction after lower third molar surgery. Nine databases (PubMed, Scopus, LILACS, SciELO, Embase, Web of Science, Cochrane, Open Gray, and Open Thesis) were used as sources of research, including “grey literature.” The protocol was registered in PROSPERO. Only randomized clinical trials evaluating the effects of preemptive intravenous ibuprofen on pain during and immediately after the extraction of lower third molars were included, without restrictions of year and language. Two reviewers independently performed the study selection, data extraction, and assessment of the risk of bias. The “Joanna Briggs Institute for Randomized Controlled Trials” tool was used to assess the risk of bias. Each study was categorized according to the percentage of positive responses to the questions corresponding to the assessment instrument. The results were measured narratively/descriptively. The initial search resulted in 3,257 records, of which only three studies (n=150 participants) met the eligibility criteria and were included in the qualitative analysis. All studies were published in 2019. The risk of bias ranged from low to moderate. Two studies found significant pain reduction within 48 h after the procedure. In conclusion, the use of preemptive intravenous ibuprofen for extracting third molars reduces pain and analgesic consumption after the surgical procedure.